Pregnancy and Perinatal Outcomes Associated with Acinetobacter baumannii Infection - Mai He; Stefan Kostadinov; Fusun Gundogan; Judith Struminsky; Halit Pinar; C. James Sung (Thieme Medical Publishers, Inc., 2013)
Abstract Objective To determine perinatal and pregnancy outcomes of Acinetobacter baumannii infection using clinicopathologic material from pregnant women, neonates, and perinatal postmortem examinations with positive cultures. Study Design This is a retrospective record review with placental and postmortem examination. Results During a 5-year period, 40 positive cultures were found. Three pregnancies with positive cultures close in the peripartum period were all associated with adverse outcomes including spontaneous abortion, preterm labor, and one full-term birth with histological chorioamnionitis. Two positive cultures were found in preterm neonates in the neonatal intensive care unit. Two of three cases of perinatal death grew pure cultures from blood and/or fetal tissue with placental or fetal examination demonstrating evidence of infection/inflammation with fetal inflammatory response. Conclusion This is the first case series report of A. baumannii-positive cultures in maternal, fetal, and neonatal specimen, with histopathologic evidence of infection. The results suggest a significant role of A. baumannii infection in adverse pregnancy and perinatal outcomes.